Six Sigma Procedures and Their Impact on the Food Industries - NOLASCO MEZARES, SILVIA JOANA; TRUJILLO VILCAPOMA, MAYIR ICOTU (LACCEI, 2025)
This study seeks to show the impact of Six Sigma (SS) procedures in the optimization of production processes in food industries. Therefore, a systematic literature review (SLR) of 172 articles was carried out. Applying the PRISMA and PICOC methodologies, 41 articles belonging to Q1 and Q2 were selected, which are aligned with the stated objective. The articles reviewed correspond to the meat, bakery, agricultural and nectar industries where SS procedures were implemented, highlighting the DMAIC procedure in 85.71% and among the benefits found, the optimization of resources, elimination of bottlenecks, cost reduction, waste minimization and increased customer satisfaction prevail. It is concluded that, the adaptation of SS through its DMAIC and DMADV procedures have a positive impact on the productive processes, which generates advantages that improve the competitiveness of each industry.